INTERAKSI ANTARA SISTEM FORMAL DENGAN BUDAYA DALAM PENCEGAHAN TINDAKAN KECURANGAN: STUDI KASUS PT BANK X (PERSERO) TBK - Maryam, Maryam; Wahyudi, Imam (Media Riset Akuntansi, 2012)
This  study  intends  to  describe,  explain  and  evaluate  fraud  prevention  system  of    a  state owned bank, namely PT Bank X (Persero) Tbk. Exploiting a case study method, researchers try  to  investigate  events  in  their  natural  contexts.  Data  were  collected  mostly  by  semi-structured  interviews  and  direct  observation  while  one  of  the  researcher  was  doing  on the  job  training  at  the  bank  for  four  months  from  2010  to  2011.  Therefore,  researcher’s own  experience  and  perception  during  the  field  observation  and  interviews  will  influence the  research  process.  The  result  shows  that  the  bank  has  successfully  implemented  three phases of fraud prevention system – detection, investigation and prevention. The interesting finding is that most  fraud cases were  detected by accident, while internal  control, internal audit  and  whistleblower  systems  that  supposed  to  be  the  most  important  devises  to  detect fraud were left behind. Cultural factors such as paternalism might explain the phenomena. Keywords: fraud  prevention  system,  case  study,  bank